Concurrent aerobic and strength training for performance in soccer - Silva, J. R. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
This chapter discusses the state of research on concurrent endurance and strength training in soccer. The first part of the chapter provides rationales for soccer as a concurrent modality and describes the physiological and performance adaptations to concurrent training in soccer. Thereafter, some considerations for training programs design will be provided, by addressing the role of the different concurrent training variables (within session order, between mode recovery length and intensity and volume) on performance outcomes and likely role on injury prevention. Because each team and athlete constitute a specific case, coaches should adopt an integrated approach when considering the concurrent training design taking into account as many related factors as possible (e.g. individual player profile, period of the season, player returning from injury or not). Abstract from author